Effect of Financial Performance and Good Corporate Governance of Bond Ratings (A Case Study Companies Listed In Indonesia Stock Exchange Period 2013-2017) - Dina Esensia; Ahmad Fauzan Fathoni; Haryetti Haryetti (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2020)
One type of investments that are considered safe and profitable is a bond. However, this investment has a risk of the company in the form of debt default risk will also affect investor decisions. Therefore, investors need to know the potential risks to be faced with analyzing the viability of the company that became a place for investment by bond rating. In addition, investors need to see whether companies apply corporate governance (GCG) or not because by implementing good corporate governance (GCG) in the company reflects that the company is able to manage efficiently the company's financial performance, including managing the assets and returns. This study aims to examine how the influence of the financial performance and good corporate governance on bond ratings. The population in this study is a company that was listed on the Indonesia Stock Exchange in 2013-2017 as many as 555 companies with a total sample of 57 companies,Sampling technique used is purposive sampling method methods of analysis used in this study is the logistic regression analysis and the results showed that financial performance variables significant negative effect on obigasi ranked. While good corporate governance variables were significant positive effect on bond ratings.